Speech and Hearing Problems Among the Mentally Retarded - Bharathraj J (Journal of All India Institute of Speech and Hearing, 1970)
Relatively few studies have been carried out in our country which throw light on the prevalence of communication disorders among Indian children. But this is felt to be an important area for survey as it would indicate the statistics about number of cases requiring diagnostic and therapeutic services in that orientation.